The Influence of Teacher Performance, Commitment, and Professionalism on Student Learning Outcomes - Yuliansyah, Muhammad; Herman, Murdiansyah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the effect of teacher performance, commitment and professionalism on student learning outcomes at SMPN 14 Banjarmasin City. This type of research is quantitative research. The population used in this study were all teachers, namely 52 teachers. Sampling in this study is by saturation sampling. The data collection technique is using a questionnaire. Methods of data analysis using multiple linear regression with the IBM SPSS statistical 22 programs. The results showed that there is an effect of performance on student learning outcomes, there is an effect of commitment on student learning outcomes, there is a professional influence of teachers on student learning outcomes, there is a simultaneous effect on performance, teacher commitment and professionalism towards student learning outcomes at SMPN 14 Banjarmasin City.